Neuraminidase inhibitors: who, when, where? - Nguyen-Van-Tam, Jonathan S.; Venkatesan, Sudhir; Muthuri, Stella G.; Myles, Puja R. (Elsevier, 2015)
Although the neuraminidase inhibitors (NIs), oseltamivir and zanamivir were first licensed in 1999, their clinical effectiveness is still hotly debated. Two rigorous systematic reviews and meta-analyses of the data from clinical trials conducted in community settings against relatively benign influenza, both suggest that reductions in symptom duration are extremely modest, under one day. Whilst one of these reviews could find no evidence of reductions in complications, the most recent review reported clinically meaningful and statistically significant reductions in the likelihood of requiring antibiotics (44%) and hospitalizations (63%) in adult patients with confirmed influenza, treated with oseltamivir. A further meta-analysis of observational data from the 2009 influenza A(H1N1) pandemic suggested that, in hospitalised patients, NIs significantly reduced mortality in adults by 25% overall, and by 62% if started within 48 hours of symptom onset, compared with no treatment. But, the effectiveness of NIs in children is far less clear. Taken together, these data suggest that NIs should be reserved for patients with influenza who are at high-risk of complications, or when clinically assessed found to be markedly unwell, or rapidly deteriorating. In such patients, treatment should be initiated empirically, as soon as possible, preferably with follow-on virological confirmation.